HOAX DI ERA DIGITAL: SOLUSI AL-QUR’AN DALAM MENYIKAPI BERITA HOAX - Istianah, Ana; Nabawiyah, Habsatun (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
Hoax is fake news that is deliberately made as if it is true news. Fake news or spread like a virus. This research is motivated by the rapid development of knowledge of technology and information, everything can be obtained quickly and instantly, as well as communication information. In the social environment, information also has an impact on the information currently circulating, especially on social media. The information circulating on social media is not known for certain. The circulation of hoax news is easy, especially in people whose literacy levels are still very low. Usually, they easily accept information for granted without checking. They disseminate it without considering the accuracy of the information it receives. The public finally fell into the confusion of news, provocation and mutual suspicion. Facing these problems, it is important to look back at the perspective of the Qur'an on the phenomenon of spreading false news. This study is important, because it is related to the position of the Qur'an which is believed to be a way of life for Muslims in Indonesia. Therefore, it is important to explore the response of the Qur'an, especially QS. An-Nur: 11 on actual phenomena such as hoaxes. So that as selective and critical Muslims we can find the best solution according to the Qur'an when dealing with various hoax news that are already rampant today.